Antiplatelet therapy increases symptomatic ICH risk after thrombolysis and thrombectomy. (27th May 2021) - Couture, Marie; Marnat, Gaultier; Griffier, Romain; Gariel, Florent; Olindo, Stéphane; Renou, Pauline; Sagnier, Sharmila; Berge, Jerome; Tourdias, Thomas; Sibon, Igor
Abstract: Background and Purpose: The influence of chronic treatment by antiplatelet drug (APD) at stroke onset on the outcomes of patients with acute ischemic stroke (AIS) treated with combined intravenous thrombolysis (IVT) and endovascular therapy (EVT) is unclear. We investigated whether prior APD use influences the risk of symptomatic intracranial hemorrhage (sICH) and functional outcome in AIS patients treated with combined reperfusion therapy. Methods: A single‐center retrospective analysis of AIS patients with proximal intracranial occlusion who underwent IVT and EVT between January 2015 and May 2017. The main outcomes were the incidence of sICH using the Heidelberg Bleeding Classification and patients' functional status at 90 days, as defined by the modified Rankin scale (mRS). Outcomes were evaluated according to daily exposure to APD, and associations were assessed using multivariate logistic regression analysis. Results: This study included 204 patients: 71 (34.8%) were taking APD before AIS. Patients with chronic treatment by APD at stroke onset had a higher rate of sICH (26.7% vs . 3.7%; p < .001) and worse functional outcome (mRS >2) at 90 days (69% vs . 36.8%; p  < .001). Prior APD use was associated with an increased likelihood of sICH (OR 9.8; 95%CI [3.6–31.3], p  < .05) and of functional dependence at 90 days (OR 5.72; 95%CI [2.09–1.72], p  < .001), independent of confounders on multivariate analysis. Conclusions: Chronic treatment by APD at stroke onset in AIS patients with proximal intracranial occlusion treated using IVT and EVT increases the risk of sICH and worsens the functional prognosis. Further investigation to refine acute revascularization strategies in this population might be required.